Els retaules de l’altar major de l’església de la Pietat de Vic. Segles XVII-XX = The high altar reredoses of La Pietat church in Vic. 17th-20th centuries - Asturiol, Elisenda (Miscel·lània litúrgica catalana, 2024)
The discovery of new documents in the archives of Vic relating to the decoration of the presbytery of that city’s La Pietat church under the advocation of Our Lady of Sorrows (Nostra Senyora de la Pietat) and of the Holy Martyrs Lucian and Marcian over the course of more than three hundred years, allows us to present new information on the reredoses of La Pietat’s high altar in the modern and contemporary periods, information which had not come to light until now.